2022
DOI: 10.3389/fpubh.2022.628791
|View full text |Cite
|
Sign up to set email alerts
|

The Analytical Framework of Governance in Health Policies in the Face of Health Emergencies: A Systematic Review

Abstract: The Governance Analytical Framework (MAG) defines governance as a social fact, endowed with analyzable and interpretable characteristics, through what it calls observable constitutive elements of governance: the problem, the actors, the social norms, the process of decision-making and scope or nodal points; in the sense that each society develops its modes of governance, its decision-making or conflict resolution systems among its members, its norms, and institutions. In this perspective, the purpose of this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Our research underscores the confluence of these multifaceted interests within the complex terrain of political decision-making. The necessity for the participation of a variety of stakeholders in the decision-making process to guarantee holistic and efficacious global health governance is apparent [ 90 ]. Nevertheless, the difficulty resides in managing the conflicting interests of these entities while aiming for collective action.…”
Section: Discussionmentioning
confidence: 99%
“…Our research underscores the confluence of these multifaceted interests within the complex terrain of political decision-making. The necessity for the participation of a variety of stakeholders in the decision-making process to guarantee holistic and efficacious global health governance is apparent [ 90 ]. Nevertheless, the difficulty resides in managing the conflicting interests of these entities while aiming for collective action.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, public health emergencies are issued in response to acts of bioterrorism, emerging infectious diseases, or other threats with a high likelihood of causing many deaths, disabilities, or exposure to harmful agents 2 . Governance in public health emergencies involves the government formulating strategic policies that meet environmental expectations 3 . Good governance cannot be achieved without the participation of broad stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…Healthy school programs across Canada demonstrated the potential for longstanding and widescale impact through cross-sector engagement between PH and education systems ( 6 ). A 2022 systematic review examining governance during public health emergencies found it is important to document how policy actors communicate and coordinate to learn effective strategies for policy implementation ( 7 ).…”
Section: Introductionmentioning
confidence: 99%